Estudo taxonômico de centopeias da família Geophilidae Leach, 1815 (Chilopoda: Geophilomorpha) de cavernas brasileiras e avaliação do seu estado de conservação - Fonseca, Régia Mayane Pacheco (2020)
Geophilidae is a diverse family with a cosmopolitan distribution. In Brazil, 11 epigean species attributed to the genera are known: Hyphydrophilus, Ribautia, Schizonampa and Geophilus. Recent research suggests the need for comprehensive taxonomic revisions in Geophilidae in order to clarify the relationships between the groups, in addition, there are few studies with species of this group in Brazil. Thus, the present study aims to studying the centipedes of the Geophilidae family occurring in Brazilian caves and to verify the existence of troglomorphic characters in the studied species. For this, 18 specimens of centipedes from 12 caves were examined and subsequently dissected. The identifications were based on identification keys and specialized bibliography. Of all the specimens, photographs and schematic drawings were made for making plates, 20 measurements of length and/or width were taken in the cave specimens and in non-cave specimens for comparative purposes in order to check if there is a tendency to stretch the appendages. Based on morphological patterns, two new species were recognized for the Hyphydrophilus, two for the Ribautia genus and a new species belonging to the Schizonampa genus, expanding the family distribution records for the Northeast and Southeast regions of the country. No troglomorphisms were found in the described species. This is the first study with geophilids from Brazilian caves, being extremely relevant for knowledge of the richness of Geophilidae species in the country and of the cavernous diversity of the sampled karst areas, supporting future studies of taxonomy and systematics of the group.